Knowledge and Attitudes of Nursing Students About Opioids and Overdose Crisis - Zarif, Madiha; Sattar, Hafsa; Fatima, Arooj; Nouman, Adeel (Biological and Clinical Sciences Research Journal, 2025)
Adequate knowledge and positive attitudes toward opioids are crucial for nursing students to provide effective pain management while minimizing the risk of opioid misuse. Understanding students’ perspectives on opioid use and overdose can help improve nursing education and patient care. Objective: To assess the knowledge and attitudes of nursing students regarding opioids and opioid overdose. Methodology: This cross-sectional study was conducted at Medicare Hospital of Nursing, Multan, from December 2023 to December 2024. A total of 100 full-time nursing students were selected. Data were collected through a 34-item questionnaire assessing demographic characteristics, knowledge, attitudes toward opioids and overdose, experience with pain management, and satisfaction with opioid policies. Responses were recorded on a Likert scale ranging from 0 (strongly disagree) to 5 (strongly agree). Statistical analysis was performed to compare knowledge and attitude scores across different academic years. Results: The mean knowledge score increased significantly with the student's educational progression, from 11.2 ± 2.76 in first-year students to 17.1 ± 2.58 in fourth-year students (f(df3) = 21.34, p<0.001). Attitudes toward opioids were negative in 50% of students overall, but this percentage declined with academic advancement: 82% of first-year, 60% of second-year, 44.5% of third-year, and 40% of fourth-year students had negative attitudes. Conclusion: Nursing students demonstrated satisfactory knowledge and a moderate attitude toward opioids, with both improving as they progressed through their academic years. However, curriculum enhancement and hands-on clinical experiences are essential to refine their understanding further and promote better patient care.